Laminated packaging material
By stacking a gas barrier layer on the polyolefin resin base film and laminating it with adhesive, the problems of single materialization and multifunctional performance of the packaging material are solved, and efficient gas barrier performance and durability are achieved, reducing the number of The early reduction of volatile ingredients provides environmentally friendly packaging materials.
Patent Information
- Application Number
- CN202380038954.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-11
- Filing Date
- 2023-04-28
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to take into account the single materialization and multifunctional properties of packaging materials, especially gas barrier properties and durability, as well as early reduction of volatile components, making it difficult to design environmentally friendly and convenient packaging materials.
By stacking a barrier layer with a gas barrier property of a predetermined range on the polyolefin resin substrate film and laminating it with the aid of an adhesive, the barrier property and durability are significantly improved, and the residual volatile components are reduced, and after the physical load is applied, the barrier property and durability are greatly improved. Maintain barrier performance.
It realizes packaging materials with less environmental load, has improved gas barrier properties and durability, reduces early reduction of volatile components, and provides an efficient packaging solution.
Smart Images

Figure BDA0005122583740000341 
Figure BDA0005122583740000342 
Figure BDA0005122583740000361
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated packaging material used in the field of packaging of food, pharmaceuticals, industrial products, etc. More specifically, it relates to an environmentally friendly laminated packaging material having excellent gas barrier properties, processability, and toughness and having convenience. Background Art
[0002] In recent years, regulations to reduce the use of disposable plastics have been strengthened in countries around the world, led by Europe. Against this backdrop, international awareness of resource recycling has increased and the garbage problem in emerging countries has become more serious. Therefore, for plastic packaging materials required for food, medicines, etc., environmentally responsive products are also required from the perspective of 3R (recycle, reuse, reduce).
[0003] As one of the possibilities for producing the above-mentioned environmentally friendly packaging materials, the packaging materials are actively studied to be formed of the same recyclable raw material, that is, to be made into a single material. As raw materials for making the single material, for example, polyester-based or polyolefin-based materials are studied.
[0004] The current situation is that packaging materials with low environmental load as described above are required, and on the other hand, for the sake of convenience, the characteristics required of the packaging materials themselves are becoming more and more functional. For example, for a bag (pouch) that can be used in a microwave oven without using aluminum foil, the bag's gas barrier, heat resistance, toughness (bag breakage resistance, pinhole resistance), high sealing, etc. are required in one packaging bag. In order to achieve this, it is necessary to bond different raw materials with different functions separately, usually with the aid of an adhesive to dry-laminate a vapor-deposited polyester film on the outside of the bag, dry-laminate a polyamide film in the middle layer, and dry-laminate a polyolefin-based heat-sealing resin on the inside (content side) to obtain a structure of at least 3 layers or more. If it is this structure, the target performance can be achieved, but because it is a bonding of different raw materials, the recyclability is poor, and there is a problem that it cannot be said to be the environmentally friendly packaging material.
[0005] In view of these points, research has been conducted on whether it is possible to design an ideal packaging material having the multifunctionality as a bag as described above even with the same raw material that can be made into a single material.
[0006] In the design of polyester-based single-material packaging materials, as an alternative to the conventional polyolefin-based sealants, a polyester-based sealant with improved low adsorption and heat resistance is disclosed (for example, see Patent Document 1). The sealant of Patent Document 1 is divided into a layer having heat sealability and other layers, and the raw material composition of these layers is separately controlled to meet the requirements of heat sealability and heat resistance. However, the heat sealability is inferior to the sealing strength of the polyolefin-based sealant, and in terms of heat resistance, the current situation is that it cannot withstand harsh treatments such as boiling and retorting.
[0007] On the other hand, in the design of polyolefin-based single-material packaging materials, polyolefin-based heat-sealing resins can be used as sealants, which have the advantage of ensuring sufficient heat-sealing properties compared to the above-mentioned polyester-based sealants. From the necessity of showing sufficient sealing properties, the sealant needs to have a certain degree of thickness and occupy a large proportion of the package body. This has also become a major reason for promoting the design of polyolefin-based single-material packaging materials. On the other hand, compared with previous packaging with barrier properties, polyolefin-based packaging materials have the problem of poor gas barrier properties. Although polypropylene film has water vapor barrier properties, it is not a sufficient value compared to, for example, transparent inorganic vapor-deposited polyester films that are generally considered to have excellent water vapor barrier properties. In addition, there is a problem of very poor oxygen barrier properties.
[0008] In contrast, a film made of a polymer resin composition generally known as having high oxygen barrier properties, such as polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polyvinylidene chloride resin, and polyacrylonitrile, is laminated on a polypropylene film (for example, refer to Patent Documents 2 to 4). However, the gas barrier coating film made of the polymer resin composition of the above-mentioned polyvinyl alcohol and ethylene-vinyl alcohol copolymer has a large humidity dependence, so a decrease in gas barrier properties is observed under high humidity, and it does not have moisture and heat resistance that can withstand sterilization treatments such as boiling and steaming. In addition, although polyvinylidene chloride resin and polyacrylonitrile have low humidity dependence, there are problems such as insufficient barrier values in absolute values and high risk of producing harmful substances during disposal / incineration. Furthermore, the heat resistance of the polypropylene film used is insufficient, and there is a problem that the film expands and contracts due to the additional heat during printing, lamination processing, and sterilization treatment, resulting in wrinkles in appearance and reduced performance.
[0009] Regarding the improvement of the gas barrier properties of polypropylene films, attempts have also been made to exhibit stable gas barrier properties without humidity dependence by laminating inorganic films (for example, Patent Document 5). However, compared with the previous polyester vapor-deposited films, there are still problems such as poor absolute values of gas barrier properties (especially oxygen barrier properties) and weak physical damage compared with the coated barrier films. In particular, polypropylene films have low dimensional stability compared with polyester films, and the films are easy to expand and contract, so there is a problem of easily causing the destruction of the barrier film. In addition, barrier materials in which polyolefin-based sealants are vapor-deposited have also been studied (for example, Patent Document 6), but there are problems such as insufficient oxygen barrier properties despite exhibiting water vapor barrier properties.
[0010] In view of the above problems, an attempt is made to further provide a protective layer with gas barrier properties on the inorganic film. For example, a method can be cited in which a water-soluble polymer, an inorganic layered compound, a metal alkoxide or its hydrolyzate are coated on an inorganic film, and a complex of an inorganic substance and a water-soluble polymer containing an inorganic layered compound is formed on an inorganic film by a sol-gel method (for example, patent document 7). The gas barrier performance can be improved by this method, and the physical damage of the inorganic film can be suppressed, but in the case of a severe physical load applied to a bending process, the current situation is that the damage to the inorganic film layer cannot be avoided. In particular, in the case of excellent barrier properties of the film itself, the film is easy to break, so there is a tendency for the barrier deterioration rate to become greater when a bending load is applied. As a drawback when the barrier properties are good, there is also a problem that when the adhesive is applied, the volatile components such as residual solvents and foaming gases are easily retained in the layer, transferred to food, and have a poor appearance. In order to reduce the volatile components, it is only necessary to extend the aging time after processing, but if it is extended, it is also possible to affect the transportation, and the current situation is that it cannot be extended to this extent. In addition, from the perspective of environmental load, the coating material used in the protective layer also needs to be environmentally friendly, and the number of processing steps for laminating the protective layer increases, and various solvents need to be used, which may cause a large load on the environment. Of course, the lamination of the protective layer also has the problem of increasing costs.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Publication No. 2017-165059
[0014] Patent Document 2: Japanese Patent Application Publication No. 2000-52501
[0015] Patent Document 3: Japanese Patent Application Laid-Open No. 4-359033
[0016] Patent Document 4: Japanese Patent Application Publication No. 2003-231221
[0017] Patent document 5: WO2017 / 221781
[0018] Patent Document 6: Japanese Patent No. 3318479
[0019] Patent Document 7: International Publication No. WO2021 / 112243 Summary of the invention
[0020] Problem that the invention aims to solve
[0021] In the above patent documents, it is difficult to achieve a single material packaging material and various properties required of packaging materials, especially gas barrier properties and durability and early reduction of residual volatile components, and it is impossible to design an environmentally friendly and convenient packaging material.
[0022] The present invention was completed against the background of the problems of the prior art. That is, the present invention aims to provide a packaging material that can form a laminated structure composed of resin types with less environmental load, improve the gas barrier performance and durability required for the packaging material, and further reduce the volatile components in the packaging material at an early stage.
[0023] Solutions for solving problems
[0024] The present inventors have found that by using a laminated film in which a barrier layer having a gas barrier performance within a predetermined range is laminated on a substrate film including a polyolefin resin layer and laminating with the aid of an adhesive, the residual volatile components can be reduced early and a significant improvement in the barrier performance after lamination can be expected, and the barrier performance can be maintained even after a physical load such as bending is applied. In addition, it has been found that by laminating a sealant including a polyolefin component, an environmentally friendly and convenient packaging material can be provided, thereby completing the present invention.
[0025] That is, the present invention is formed by the following technical solutions.
[0026] 1. A laminated packaging material, characterized in that: it is a laminated packaging material having an adhesive layer, a heat-sealable resin layer and at least one substrate film, the substrate film having a resin layer with a polyolefin resin as a main component, at least one of the substrate films is a laminated gas barrier film having a gas barrier layer, and the oxygen permeability value (A) measured under 23°C × 65%RH for the substrate film (a) with the lowest oxygen permeability among the laminated substrate films alone is 30 to 1500 ml / m 2 ·d·MPa, under the same conditions, the oxygen permeability value (P) of the laminated packaging material (p) formed by laminating the base film and the heat-sealing resin via the adhesive layer was 60 ml / m 2·d·MPa or less, and the barrier value improvement rate before and after lamination represented by the following formula (1) is 10 or more.
[0027] Barrier value improvement rate before and after film lamination = (A / P) ... Formula (1)
[0028] 2. The laminated packaging material according to 1., characterized in that: the oxygen permeability value (G) of the laminated packaging material after 25 torsion bending tests at a temperature of 23°C using a rubbing tester is 65 ml / m 2 ·d·MPa or less.
[0029] 3. The laminated packaging material according to 1. or 2., characterized in that the time required from the moment the laminated packaging material (p) is produced by bonding the base film and the heat-sealing resin with the aid of an adhesive until the volatile components cease to volatilize and disappear is within 30 hours.
[0030] 4. A laminated packaging material according to any one of 1. to 3., wherein the substrate film comprises the substrate film (a) and another substrate film (b), the substrate film (b) is a laminated barrier film having a resin layer and a gas barrier layer, and the resin layers constituting the substrate film (a) and the substrate film (b) have the same polyolefin resin as a main constituent.
[0031] 5. The laminated packaging material according to any one of 1. to 4., comprising two or less substrate films.
[0032] 6. The laminated packaging material according to any one of 1. to 5., wherein the resin layer constituting the base film and the heat-sealable resin layer contain the same polyolefin-based resin as a main constituent component.
[0033] 7. The laminated packaging material according to any one of 1. to 6., wherein the adhesive layer is formed of any one of polyurethane-based, polyester-based, and polyamine-based resins.
[0034] 8. The laminated packaging material according to any one of 1. to 7., wherein the gas barrier layer is an inorganic thin film layer formed of any one of aluminum, aluminum oxide, silicon oxide, or a composite oxide of silicon oxide and aluminum oxide.
[0035] 9. The laminated packaging material according to any one of 1. to 8., wherein the gas barrier layer is a covering layer formed of any one of a polyvinyl alcohol resin, a polyester resin, and a polyurethane resin.
[0036] 10. The laminated packaging material according to any one of 1. to 9., wherein an anchor coating layer is laminated between the base film and the gas barrier layer.
[0037] 11. The laminated packaging material according to any one of 1. to 10., characterized in that it is used for boiling or steaming.
[0038] 12. The laminated packaging material according to any one of 1. to 10., characterized in that it is used for heating in a microwave oven.
[0039] 13. A packaging bag, comprising the laminated packaging material according to any one of 1. to 12.
[0040] 14. A packaging body obtained by packaging an object using the laminated packaging material according to any one of 1. to 12. or the packaging bag according to 13.
[0041] Effects of the Invention
[0042] The present inventors have been able to provide a packaging material having the barrier properties and durability required for packaging materials and having a low volatile content, while taking the environment into consideration, by using such a technique. DETAILED DESCRIPTION
[0043] The packaging material of the present invention is characterized in that: it is a laminated packaging material having an adhesive layer, a heat-sealable resin layer and at least one substrate film, the substrate film having a resin layer with a polyolefin resin as a main component, at least one of the substrate films is a laminated gas barrier film having a gas barrier layer, and the oxygen permeability value (A) measured under 23°C × 65%RH for the substrate film (a) having the lowest oxygen permeability among the substrate films alone is 30 to 1500 ml / m 2 ·d·MPa, when the value of oxygen permeability measured for a laminated packaging material (p) formed by laminating a base film and a heat-sealable resin via an adhesive layer under the same conditions is defined as (P), the barrier value improvement rate before and after lamination is 10 or more. It should be noted that the term "mainly composed of..." means that it contains 50% by mass or more in the constituent components.
[0044] Hereinafter, the present invention will be described in detail.
[0045] [Base film with polyolefin resin as main component]
[0046] The packaging material of the present invention has a substrate film with a polyolefin resin as the main constituent component. The substrate film is preferably a substrate film with a polypropylene resin as the main constituent component (hereinafter referred to as a polypropylene resin film), and is more preferably a stretched film. The polypropylene resin stretched film used as the substrate film in the present invention is preferably a biaxially stretched film. As a biaxially stretched polypropylene resin film, a known biaxially stretched polypropylene resin film can be used, and its raw materials, mixing ratio, etc. are not particularly limited. For example, in addition to a polypropylene homopolymer (propylene homopolymer), it can also be a mixture of propylene as the main component and one or more random copolymers, block copolymers, etc. selected from α-olefins such as ethylene, butene, pentene, hexene, etc., or a mixture of these polymers mixed with more than two kinds. In addition, for the purpose of modifying physical properties, known additives such as antioxidants, antistatic agents, plasticizers, etc. can be added, for example, petroleum resins, terpene resins, etc. can be added.
[0047] In the present invention, the polypropylene resin constituting the substrate film is preferably a propylene homopolymer substantially free of comonomers other than propylene. Even if a comonomer is contained, the amount of the comonomer is preferably less than 0.5 mol%. The upper limit of the amount of the comonomer is more preferably 0.3 mol%, and further preferably 0.1 mol%. If it is within the above range, the crystallinity is improved, the dimensional change at high temperature is reduced, that is, the elongation when heated to a certain temperature (hereinafter referred to as the heating elongation) is reduced, and the heat resistance is improved. By improving the heat resistance, the lamination process of the barrier layer is stabilized, and as a result, the barrier performance can be stabilized. It should be noted that the comonomer can be included as long as it is a trace amount within the range that does not significantly reduce the crystallinity.
[0048] In addition, the biaxially stretched polypropylene resin film used in the present invention may be a monolayer film or a laminated film. However, in order to achieve the purpose of the present invention, a laminated film is preferred. The type, number of layers, and lamination method of the laminate are not particularly limited and can be arbitrarily selected from known methods. It is preferred to improve the lamination strength and the bonding strength of the coating agent by controlling the surface roughness and flexibility of the substrate film surface.
[0049] As a method of improving the lamination strength of the substrate film and the interfacial bonding strength with the inorganic thin film layer, coating agent, etc., a mixture of two or more polypropylene resins having different melt flow rates (MFR) can be used as the polypropylene resin constituting the surface layer of the substrate film.
[0050] It is speculated that when the difference in melt flow rate (MFR) between two or more polypropylene resins in a mixture of polypropylene resins is small, the crystallization rate and crystallinity of each polypropylene resin are not significantly different, and minute irregularities are easily generated on the surface. However, if the cooling rate of the unstretched sheet is slow during the manufacture of the film, the surface irregularities caused by spherulites become larger, and if the stretching temperature is too high during longitudinal stretching or transverse stretching, the surface irregularities are likely to become larger, so it is necessary to pay attention.
[0051] As each polypropylene resin, a polypropylene homopolymer containing no copolymerization component and a polypropylene resin obtained by copolymerizing ethylene and / or an α-olefin having a carbon number of 4 or more at a ratio of 5.0 mol% or less can be used. The copolymerization component of the copolymerized polypropylene resin is preferably 4.0 mol% or less, more preferably 3.5 mol% or less. The copolymerization component of the copolymerized polypropylene resin is preferably 1.0 mol% or more, more preferably 1.5 mol% or more, further preferably 2.0 mol% or more, and particularly preferably 2.5 mol% or more.
[0052] Examples of the α-olefin having 4 or more carbon atoms include 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. In addition, polar maleic acid, etc. may be used as other copolymerization components.
[0053] The lower limit of the xylene soluble component of the polypropylene resin constituting the substrate film is preferably 0.1% by mass from a practical point of view. The upper limit of the xylene soluble component is preferably 7% by mass, more preferably 6% by mass, and further preferably 5% by mass. If it is within the above range, the crystallinity is improved, the elongation after heating becomes smaller, and the heat resistance is improved.
[0054] In the present invention, the lower limit of the melt flow rate (MFR) (230°C, 2.16kgf) of the polypropylene resin is preferably 0.5g / 10min. The lower limit of MFR is more preferably 1.0g / 10min, further preferably 2.0g / 10min, particularly preferably 4.0g / 10min, and most preferably 6.0g / 10min. If it is within the above range, the mechanical load is small, and extrusion and stretching become easy. The upper limit of MFR is preferably 20g / 10min. The upper limit of MFR is more preferably 17g / 10min, further preferably 16g / 10min, and particularly preferably 15g / 10min. If it is within the above range, stretching becomes easy, thickness unevenness becomes smaller, or the stretching temperature and heat setting temperature are easily increased, the heating elongation becomes smaller, and the heat resistance is improved.
[0055] From the viewpoint of heat resistance, the substrate film can be a uniaxially stretched film in the longitudinal direction (MD direction) or the transverse direction (TD direction), preferably a biaxially stretched film. In the present invention, by using the preferred raw materials to perform at least uniaxial stretching, a film having a low thermal elongation at high temperature and high heat resistance that is unpredictable for conventional polypropylene films can be obtained. As stretching methods, simultaneous biaxial stretching methods, successive biaxial stretching methods, etc. can be cited. From the aspects of making planarity, dimensional stability, uneven thickness, etc. good, the successive biaxial stretching method is preferred.
[0056] As a sequential biaxial stretching method, a polypropylene resin is heated and melted by a uniaxial or biaxial extruder in such a manner that the resin temperature reaches 200°C or more and 280°C or less, and a sheet is formed by a T-die, and extruded onto a cooling roll at a temperature of 10°C or more and 100°C or less to obtain an unstretched sheet. Next, the sheet may be roll stretched to 3.0 times or more and 8.0 times or less at a temperature of 120°C or more and 165°C or less in the longitudinal direction (MD direction), and then, after preheating with a tenter, the sheet may be stretched to 4.0 times or more and 20.0 times or less at a temperature of 155°C or more and 175°C or less in the transverse direction (TD direction). Furthermore, after biaxial stretching, a heat setting treatment may be performed while allowing 1% or more and 15% or less relaxation at a temperature of 165°C or more and 175°C or less.
[0057] In order to make the heating elongation percentage in the above range, the base film of the present invention is preferably formed by the following method.
[0058] First, the upper limit of the stretching temperature in the length direction (MD) is preferably the film melting point (Tm) -7 ° C, more preferably Tm - 10 ° C, and further preferably Tm - 12 ° C. If it is in the above range, it is easy to reduce the heating elongation, and it is difficult to weld with the stretching roller for stretching, so the quality is less reduced. It should be noted that the stretching in the length direction can be stretched using more than 3 pairs of stretching rollers, divided into more than 2 stages for multi-stage stretching. By dividing it into multiple stages, the strain during stretching can be reduced, so it is easy to reduce the heating elongation.
[0059] The upper limit of the stretching ratio in the width direction (TD) is preferably 15 times, more preferably 12 times, and further preferably 10 times. If it exceeds the above, the elongation during heating becomes high and the film is easily broken during stretching.
[0060] In addition, the lower limit of the TD stretching temperature is preferably 150°C, more preferably 152°C, further preferably 154°C, and particularly preferably 156°C. If it is 150°C or more, it is stretched in a fully softened state, so it is easy to reduce the heating elongation. The upper limit of the TD stretching temperature is preferably 164°C, more preferably 162°C, and further preferably 160°C. In order to reduce the heating elongation, it is preferred that the temperature is high.
[0061] The lower limit of the heat setting temperature after stretching in the width direction (TD) is preferably 168° C., more preferably 170° C., and further preferably 173° C. When it is 168° C. or higher, the heat elongation is unlikely to increase, and a long treatment period is not required to reduce the heat elongation.
[0062] It is preferred to relax (relax) the material during heat setting. The lower limit of the relaxation rate is preferably 2%, more preferably 3%. If the relaxation rate is less than the above range, the elongation during heating may become high.
[0063] Furthermore, in order to reduce the heat shrinkage, the film produced in the above step may be temporarily wound into a roll and then annealed off-line.
[0064] In order to impart handling properties (for example, windability after lamination), the substrate film used in the present invention preferably contains particles to form protrusions on the film surface. Particles contained in the film include inorganic particles such as silica, kaolinite, talc, calcium carbonate, zeolite, and alumina; heat-resistant polymer particles such as acrylic, PMMA, nylon, polystyrene, polyester, and benzoguanamine-formaldehyde condensate. From the perspective of transparency, the content of particles in the film is preferably small, for example, preferably more than 1 ppm and less than 1000 ppm. In addition, the preferred average particle size of the particles is 1.0 to 3.0 μm, more preferably 1.0 to 2.7 μm. The method for determining the average particle size here is a method of taking a photograph with a scanning electron microscope, measuring the Feret diameter in the horizontal direction using an image analyzer device, and expressing it with its average value. Furthermore, from the perspective of transparency, it is preferred to select particles whose refractive index is close to that of the resin used. In order to impart various functions as required, the film may contain antioxidants, ultraviolet absorbers, antistatic agents, pigments, lubricants, nucleating agents, adhesives, antifogging agents, flame retardants, antiblocking agents, inorganic or organic fillers, etc.
[0065] In addition to the polypropylene resin used in the present invention, other resins may be used for the purpose of improving the mechanical properties of the substrate film, improving the adhesion with the ink layer and adhesive layer laminated on the gas barrier coating layer, reducing the environmental load, etc., within the range that does not impair the purpose of the present invention. For example, polyethylene resins, polypropylene resins different from the above, random copolymers that are copolymers of propylene and ethylene and / or α-olefins having 4 or more carbon atoms, various elastomers, etc. may be mentioned.
[0066] The polyethylene resin that can be used for the substrate film in the present invention is a resin with ethylene as the main component. For example, in addition to using any ethylene homopolymer such as high-pressure low-density polyethylene, linear low-density polyethylene, medium-density polyethylene and high-density polyethylene, crystalline or low-crystalline or non-crystalline random or block copolymers with α-olefins such as propylene, 1-butene, 1-pentene, 1-hexene, 3-methyl-1-butene, 4-methyl-1-pentene, 1-octene, vinyl acetate, (meth)acrylic acid, (meth)acrylates, or mixtures thereof can also be used.
[0067] The polyethylene resin is preferably contained in an amount of 1% by weight or more and 25% by weight or less relative to the total of 100 of the polypropylene resin and the polyethylene resin constituting the substrate. If it is 1% by weight or more, the heat seal strength, anti-blocking property and anti-fogging property are improved. More preferably, it is 5% by weight or more, and more preferably, it is 8% by weight or more. If it is 20% by weight or less, it is easy to maintain rigidity. More preferably, it is 18% by weight or less, and more preferably, it is 15% by weight or less.
[0068] The melting point of the polyethylene resin is preferably in the range of 100°C to 135°C, more preferably in the range of 105°C to 130°C, from the viewpoints of heat resistance, transparency, mechanical properties, and film forming properties. The density is preferably 0.90 g / cm 3 Above 0.94g / cm 3 Below, more preferably 0.91 g / cm 3 Above 0.94g / cm 3 the following.
[0069] The melt flow rate (MFR) (190°C, 2.16 kgf) of the polyethylene resin is preferably 0.5 g / 10 min or more, more preferably 1 g / 10 min or more, and further preferably 2 g / 10 min or more. From the viewpoint of further stabilizing the moldability, it is preferably 20 g / 10 min or less, more preferably 15 g / 10 min or less, and further preferably 10 g / 10 min or less.
[0070] From the viewpoint of low environmental load, the polyethylene resin of the present invention can use a polyethylene resin derived from plants. The biobase content of the polyethylene resin measured according to ISO16620 is preferably 50% to 100%, preferably 70% to 100%, and more preferably 80% to 100%.
[0071] In the present invention, the thickness of the substrate film is arbitrarily set according to each purpose, and the lower limit is preferably 2 μm or more, more preferably 3 μm or more, and further preferably 4 μm or more. On the other hand, the upper limit of the thickness is preferably 300 μm or less, more preferably 250 μm or less, further preferably 200 μm or less, and particularly preferably 150 μm or less. In the case of thin thickness, the handling property is prone to become poor. On the other hand, in the case of thick thickness, not only there are problems in terms of cost, but also in the case of winding into a roll for storage, it is easy to produce poor planarity caused by the rolling habit.
[0072] From the viewpoint of visibility of the contents, the haze of the substrate film of the present invention is preferably transparent, specifically, preferably 6% or less, more preferably 5% or less, and further preferably 4% or less. For example, when the stretching temperature or heat setting temperature is too high, when the cooling roll (CR) temperature is high, when the cooling speed of the stretched original roll is slow, and when the low molecular weight is too high, there is a tendency for the haze to deteriorate, and therefore, by adjusting these, it can be controlled within the above range.
[0073] In addition, as long as the purpose of the present invention is not impaired, the base film layer in the present invention may be subjected to corona discharge treatment, glow discharge treatment, flame treatment, surface roughening treatment, and may also be subjected to known anchor coating treatment, printing, decoration, etc. In the anchor coating, a resin with good adhesion such as polyurethane and polyester is generally suitable, and the anchor coating used to improve the barrier in the present invention will be described later.
[0074] The packaging material of the present invention requires at least one substrate film having a gas barrier layer, but by laminating more than two substrate films, it is expected that the toughness and gas barrier performance of the packaging material can be improved, so it can be used according to the purpose. In terms of toughness, by using two polypropylene biaxially stretched films that generally have the characteristic of high puncture strength, it is possible to achieve a packaging material design that is not inferior to the structure of two different raw materials used for polyester films and polyamide films widely used as packaging materials. In addition, in terms of gas barrier properties, by using two substrate films, the film in the middle is not easily affected by the external environment, such as temperature and humidity, external bending, etc., and can exert a more stable gas barrier performance. In this sense, when using two substrate films, the covering layer and inorganic film layer with gas barrier performance are particularly preferably laminated on the middle film.
[0075] [Gas barrier layer]
[0076] In the present invention, at least one of the above-mentioned substrate films needs to be a laminated substrate film having a gas barrier layer. It should be noted that as the gas barrier layer, it is necessary to laminate any one of the cover layer (A) having an organic substance as a main component or the inorganic thin film layer (B) having an inorganic substance as a main component. Furthermore, for the purpose of assisting the barrier properties of the gas barrier layer, the anchor coating layer (C) described below may be used in combination with a protective layer and laminated to protect the barrier layer.
[0077] [Coating layer (A)]
[0078] In the present invention, a covering layer (A) may be provided as a gas barrier layer. However, in the present invention, it is necessary to design the film with consideration of the environmental loads such as the increase in cost due to the increase in steps caused by providing the covering layer (A) and the difficulty in recycling due to the film thickness.
[0079] The coating weight of the coating layer (A) is preferably 0.10 to 0.70 (g / m 2 The lower limit of the amount of coating layer (A) is preferably 0.15 (g / m 2 ) or more, more preferably 0.20 (g / m 2 ) or more, more preferably 0.25 (g / m 2 ) or more, and the upper limit is preferably 0.65 (g / m 2 ) or less, more preferably 0.60 (g / m 2 ) or less, more preferably 0.55 (g / m 2 ) or less. If the coating weight of the coating layer (A) exceeds 0.70 (g / m 2 ), the gas barrier properties are improved, but the cohesive force inside the covering layer becomes insufficient, and the uniformity of the covering layer is also reduced, so sometimes unevenness (increased haze, whitening) or defects occur in the coating appearance, or the gas barrier properties / adhesion cannot be fully demonstrated. In addition, in terms of processability, adhesion may also occur due to the thick film thickness. Furthermore, there is a concern that the recyclability of the film will be adversely affected, and the amount of raw materials / solvents used will also increase, so the environmental load becomes stronger. On the other hand, if the film thickness of the covering layer (A) is less than 0.10 (g / m 2 ), sufficient gas barrier properties and interlayer adhesion may not be obtained.
[0080] As the resin composition used in the covering layer (A) formed on the surface of the laminated film of the present invention, a polyvinyl alcohol polymer is ideal. The polyvinyl alcohol polymer has vinyl alcohol units as the main constituent components, and it can be expected that the barrier performance will be greatly improved due to the high cohesion brought about by the hydrogen bond structure. The degree of polymerization and saponification of the polyvinyl alcohol polymer are determined by the target gas barrier properties and the viscosity of the coating aqueous solution. Regarding the degree of polymerization, since the aqueous solution has a high viscosity and is easy to gel, it becomes difficult to apply. From the perspective of coating workability, it is preferably 2600 or less. Regarding the saponification degree, when it is less than 90%, sufficient oxygen barrier properties under high humidity cannot be obtained. If it exceeds 99.7%, the adjustment of the aqueous solution is difficult, it is easy to gel, and it is not suitable for industrial production. Therefore, the saponification degree is preferably 90 to 99.7%, and more preferably 93 to 99%. In addition, in the present invention, various copolymerized or modified polyvinyl alcohol polymers such as polyvinyl alcohol polymers copolymerized with ethylene and polyvinyl alcohol polymers modified with silanol can also be used within the range that does not damage processability and productivity.
[0081] The cover layer (A) of the present invention may contain an inorganic layered compound. By the presence of an inorganic layered compound, a labyrinth effect on gas can be expected to improve gas barrier properties. In addition, by adding an inorganic layered compound, the humidity dependence of gas barrier properties can be suppressed. As materials, clay minerals such as smectite, kaolin, mica, hydrotalcite, and chlorite (including synthetic products thereof) can be listed. Specifically, montmorillonite, beidellite, saponite, hectorite, zinc soapstone, stony soapstone, kaolinite, perlite, dickite, halloysite, hydrated halloysite, tetrasilicon mica, sodium band mica, muscovite, pearl mica, phlogopite, talc, antigorite, serpentine, pyrophyllite, vermiculite, sorbite, chlorite, etc. can be listed. Furthermore, as an inorganic layered compound, flaky silica, etc. can also be used. These can be used alone or in combination of two or more. Among them, montmorillonite (including synthetic products thereof) is particularly preferred because of its high effect of improving water vapor barrier properties.
[0082] In addition, as an inorganic layered compound, it is preferred that a metal ion having redox properties, particularly an iron ion, is present therein. Furthermore, among such substances, montmorillonite, which is a type of montmorillonite, is preferred from the aspects of coating adaptability and gas barrier properties. As montmorillonite, a known substance that has been used as a gas barrier agent can be used.
[0083] For example, the following general formula:
[0084] (X,Y) 2~3 Z4O 10 (OH)2·mH2O·(Wω)
[0085] (In the formula, X represents Al, Fe(III) or Cr(III). Y represents Mg, Fe(II), Mn(II), Ni, Zn or Li. Z represents Si or Al. W represents K, Na or Ca. H2O represents interlayer water. m and ω represent positive real numbers.)
[0086] Among them, from the viewpoint of dissociation in an aqueous medium, it is preferred that W in the formula is Na.
[0087] The size and shape of the inorganic layered compound are not particularly limited. As a particle size (major diameter), it is preferably 5 μm or less, more preferably 4 μm or less, and further preferably 3 μm or less. If the particle size is greater than 5 μm, the dispersibility is poor, and as a result, the coating property and coating appearance of the covering layer (A) may be deteriorated. On the other hand, as its aspect ratio, it is 50 to 5000, more preferably 100 to 4000, and further preferably 200 to 3000.
[0088] The blending ratio of the resin composition and the inorganic layered compound in the covering layer of the present invention is preferably 75 / 25 to 35 / 65 (wt%), more preferably 70 / 30 to 40 / 60 (wt%), and further preferably 65 / 35 to 45 / 55 (wt%). If the blending ratio of the inorganic layered compound is less than 25%, the barrier performance may be insufficient. On the other hand, if it is more than 65%, the dispersibility may deteriorate and the coating property may deteriorate, and the adhesion may deteriorate.
[0089] In the covering layer (A) of the present invention, various crosslinking agents may be added within a range that does not impair the gas barrier properties and productivity in order to improve the cohesive force and moisture-heat resistant adhesion of the film. Examples of the crosslinking agent include silicon-based crosslinking agents, oxazoline compounds, carbodiimide compounds, epoxy compounds, isocyanate compounds, and the like. Among them, by adding a silicon-based crosslinking agent, a crosslinking reaction can be carried out with a resin composition having a hydroxyl group and an inorganic thin film layer. From the viewpoint of improving water-resistant adhesion, a silicon-based crosslinking agent is particularly preferred. Commonly used silicon-based crosslinking agents include metal alkoxides and silane coupling agents. Metal alkoxides are represented by the general formula M(OR) n(M: metal of Si, Al, R: alkyl such as CH3, C2H5) represented by a compound. Specifically, tetraethoxysilane〔Si(OC2H5)4〕, triisopropoxyaluminum Al[OCH(CH3)2]3, etc. can be exemplified. As a silane coupling agent, silane coupling agents having epoxy groups such as 3-glycidyloxypropyltrimethoxysilane, silane coupling agents having amino groups such as 3-aminopropyltrimethoxysilane, silane coupling agents having mercapto groups such as 3-mercaptopropyltrimethoxysilane, silane coupling agents having isocyanate groups such as 3-isocyanatepropyltriethoxysilane, tris(3-trimethoxysilylpropyl)isocyanurate, etc. can be exemplified. In addition, as a crosslinking agent, oxazoline compounds, carbodiimide compounds, epoxy compounds, etc. can also be used in combination. However, in the case of attaching importance to recyclability, it is necessary to consider the amount of the crosslinking agent.
[0090] When the crosslinking agent is mixed, the amount thereof is preferably 0.05 to 4.00% by mass in the covering layer, more preferably 0.10 to 3.50% by mass, and further preferably 0.15 to 3.00% by mass. By setting the above range, the film is cured, the cohesion is improved, and as a result, a film with excellent water-resistant adhesiveness can be made. If the amount of the mixture exceeds 3.00% by mass, the amount of the uncrosslinked part increases, the curing is excessively performed, and the film hardens, thereby the adhesiveness may be reduced. On the other hand, if the amount of the mixture is less than 0.05% by mass, sufficient cohesion may not be obtained.
[0091] In the present invention, from the viewpoint of visibility of the contents, the haze of the film after the covering layer (A) is laminated is preferably 20% or less, more preferably 18% or less, and further preferably 16% or less. If the haze is greater than 20%, the transparency is greatly deteriorated, and on this basis, the surface unevenness may also be affected, which may lead to poor appearance in subsequent printing processes, etc. It should be noted that the haze can be adjusted by the composition ratio of the covering layer (A), solvent conditions, film thickness, etc. Here, the haze is evaluated according to JIS K7136 using a turbidity meter (Nippon Denshoku, NDH2000).
[0092] The coating method of the coating layer resin composition is not particularly limited as long as it is a method of coating the film surface to form a layer. For example, a common coating method such as gravure coating, reverse roll coating, wire bar coating, die coating, etc. can be used.
[0093] When forming the covering layer (A), it is preferred to pre-dry at a relatively low temperature after applying the resin composition for the covering layer, first volatilize the solvent, and then perform main drying at a high temperature, because a uniform film can be obtained. The pre-drying temperature is preferably 80 to 110°C, more preferably 85 to 105°C, and further preferably 90 to 100°C. If the pre-drying temperature is lower than 80°C, insufficient drying may occur in the covering layer. In addition, if the pre-drying temperature is higher than 110°C, drying is performed before the covering layer is wet and spread, which may result in poor appearance.
[0094] On the other hand, the main drying temperature is preferably 110 to 140° C., more preferably 115 to 135° C., and even more preferably 120 to 130° C. If the main drying temperature is lower than 110° C., the film formation of the cover layer (A) does not proceed, and the cohesive force and adhesiveness decrease, which may result in an adverse effect on the barrier properties. If it exceeds 140° C., the film may be overheated and become brittle, or wrinkles due to heat shrinkage may become larger.
[0095] The preferred drying time for pre-drying is 3.0 to 10.0 seconds, more preferably 3.5 to 9.5 seconds, and further preferably 4.0 to 9.0 seconds. In addition, the preferred drying time for main drying is 3.0 to 10.0 seconds, more preferably 3.5 to 9.5 seconds, and further preferably 4.0 to 9.0 seconds. However, the drying conditions also vary depending on the type of heat medium and the intake and exhaust conditions of the drying furnace, so attention should be paid. In addition, unlike drying, additional heat treatment in a low temperature range, specifically in a temperature range of 40 to 60°C for 1 to 4 days is also more effective in film formation of the covering layer (A).
[0096] [Inorganic thin film layer (B)]
[0097] In the present invention, as a gas barrier layer, an inorganic thin film layer (B) may be provided on the surface of the above-mentioned substrate film. The inorganic thin film layer (B) is a thin film formed of a metal or an inorganic oxide. The material forming the inorganic thin film layer is not particularly limited as long as it can be made into a thin film. From the viewpoint of gas barrier properties, inorganic oxides such as silicon oxide (silicon dioxide), aluminum oxide (alumina), and a mixture of silicon oxide and aluminum oxide can be preferably cited. In particular, from the perspective of being able to take into account the softness and density of the film layer, a composite oxide of silicon oxide and aluminum oxide is preferably used. In this composite oxide, the mixing ratio of silicon oxide and aluminum oxide is preferably in the range of 20 to 70% by mass of Al in terms of the mass ratio of the metal components. If the Al concentration is less than 20% by mass, the water vapor barrier property sometimes decreases. On the other hand, if it exceeds 70% by mass, there is a tendency for the inorganic thin film layer to harden, and it is possible that the film is destroyed and the gas barrier property is reduced during secondary processing such as printing and lamination. It should be noted that the silicon oxide mentioned here refers to various silicon oxides such as SiO and SiO2 or mixtures thereof, and the aluminum oxide refers to various aluminum oxides such as AlO and Al2O3 or mixtures thereof.
[0098] The film thickness of the inorganic thin film layer (B) is usually 1 to 100 nm, preferably 5 to 50 nm. If the film thickness of the inorganic thin film layer (B) is less than 1 nm, it is sometimes difficult to obtain satisfactory gas barrier properties. On the other hand, even if it is too thick exceeding 100 nm, it is impossible to obtain a comparable improvement in gas barrier properties, which is disadvantageous in terms of bending resistance and manufacturing cost.
[0099] There is no particular limitation on the method for forming the inorganic thin film layer (B), and any known evaporation method such as physical evaporation method (PVD method) such as vacuum evaporation method, sputtering method, ion plating method, or chemical evaporation method (CVD method) can be appropriately used. Below, a typical method for forming an inorganic thin film layer (B) is described by taking silicon oxide and aluminum oxide thin films as examples. For example, when a vacuum evaporation method is used, a mixture of SiO2 and Al2O3, or a mixture of SiO2 and Al, etc. is preferably used as the evaporation raw material. As these evaporation raw materials, particles are usually used. At this time, the size of each particle is the size to which the pressure does not change during evaporation. The preferred particle size is 1mm to 5mm. Heating can be performed by resistance heating, high-frequency induction heating, electron beam heating, laser heating, etc. In addition, reactive evaporation by introducing oxygen, nitrogen, hydrogen, argon, carbon dioxide, water vapor, etc. as reaction gases, or by using ozone addition, ion assistance, etc. Furthermore, the film forming conditions can be arbitrarily changed by applying a bias voltage to the vapor-deposited body (the laminated thin film for vapor deposition), or by heating or cooling the vapor-deposited body. Such vapor deposition materials, reaction gases, bias voltage, heating / cooling of the vapor-deposited body, etc. can also be changed in the same manner when sputtering or CVD is used.
[0100] [Anchor coating (C)]
[0101] In the present invention, as an auxiliary layer for showing sufficient gas barrier and adhesion when stacking the above-mentioned gas barrier layer, an anchor coating (C) can be provided. By having an anchor coating, it is possible to suppress oligomers and anti-adhesion materials from being exposed from polypropylene resin. And then, when stacking other layers on the anchor coating (C), the interlayer adhesion can also be improved. In particular, in the formation of the inorganic film layer, not only by adhesion, but also by promoting the formation of the inorganic layer by smoothing the surface, it is possible to expect the effect of improved gas barrier. On this basis, by using a material that also has a certain degree of gas barrier (set as gas barrier auxiliary) in the anchor coating (C) itself, it is also possible to significantly improve the gas barrier performance of the film when stacking the gas barrier layer.
[0102] As the gas barrier auxiliary property of the film when only the anchor coating layer (C) is laminated, it is preferred that the oxygen permeability under 23°C×65%RH environment is 10000ml / m 2 ·d·MPa or less. More preferably, 9000ml / m 2 ·d·MPa or less, more preferably 8000ml / m 2 ·d·MPa or less. If the oxygen permeability exceeds 10000ml / m 2 ·d·MPa, even after laminating the gas barrier layer, sufficient barrier performance cannot be obtained, and it is difficult to cope with applications requiring high gas barrier properties.
[0103] In the present invention, it is preferred that the adhesion amount of the anchor coating layer (C) be 0.10 to 0.50 g / m 2 As a result, the anchor coating (C) can be uniformly controlled during coating, resulting in a film with less uneven coating and fewer defects. Furthermore, the anchor coating (C) helps to suppress the exposure of oligomers and stabilize the haze after wet heat treatment. The adhesion amount of the anchor coating (C) is preferably 0.15 g / m 2 More preferably 0.20 g / m 2 More preferably, 0.35 g / m 2 Above, preferably 0.50g / m 2 Below, more preferably less than 0.45g / m 2 Below, more preferably 0.40g / m 2 If the anchor coating (C) adhesion exceeds 0.50 g / m 2, the gas barrier assistance is improved, but the cohesive force inside the anchor coating becomes insufficient, and the uniformity of the anchor coating is also reduced, so the coating appearance is uneven and defective. In addition, in terms of processability, due to the thick film thickness, adhesion may occur or manufacturing costs may be incurred. Furthermore, there are concerns that the recyclability of the film may be adversely affected, and the amount of raw materials / solvents used may also increase, so the environmental load becomes stronger. On the other hand, if the film thickness of the anchor coating (C) is less than 0.10g / m 2 , it may not be possible to obtain sufficient gas barrier assistance and interlayer adhesion.
[0104] The resin composition used in the anchor coating (C) of the present invention includes a resin composition obtained by adding epoxy, isocyanate, melamine or other curing agents to urethane, polyester, acrylic, titanium, isocyanate, imine, polybutadiene or other resins. It may also contain a crosslinking agent such as a silicon crosslinking agent, an oxazoline compound, a carbodiimide compound, or an epoxy compound.
[0105] In particular, when a urethane resin is contained, the polar group interacts with the inorganic thin film layer on the basis of the barrier performance brought by the high cohesion of the urethane bond itself, and it also has flexibility due to the presence of the amorphous part, so it can suppress damage even when a bending load is applied, so it is preferred. In addition, polyester resin can also be expected to have the same effect, so it is suitable. In the present invention, it is particularly preferred to contain a polyurethane composed of polyester + isocyanate, and further, from the viewpoint of being able to improve adhesion, it is more preferred to add a silicon-based crosslinking agent.
[0106] The urethane resin used in the anchor coating (C) of the present invention is preferably a urethane resin containing an aromatic or aromatic aliphatic diisocyanate component as a main component from the perspective of gas barrier assistance. Among them, it is particularly preferred to contain meta-xylylene diisocyanate. By using the above resin, the cohesive force of the urethane bond can be further improved by utilizing the stacking effect of the aromatic rings, resulting in good gas barrier assistance.
[0107] In the present invention, the proportion of the aromatic or aromatic aliphatic diisocyanate in the urethane resin used in the anchor coating (C) is preferably set to a range of 50 mol% or more (50 to 100 mol%) in 100 mol% of the polyisocyanate component. The total amount of the aromatic or aromatic aliphatic diisocyanate is preferably 60 to 100 mol%, more preferably 70 to 100 mol%, and further preferably 80 to 100 mol%. If the total amount of the aromatic or aromatic aliphatic diisocyanate is less than 50 mol%, it is possible that good gas barrier auxiliary properties cannot be obtained.
[0108] In the carbamate resin used in the anchor coating (C) of the present invention, various crosslinking agents can be mixed in order to improve the cohesive force of the film and improve the moisture-heat-resistant adhesion. As a crosslinking agent, for example, a silicon-based crosslinking agent, an oxazoline compound, a carbodiimide compound, an epoxy compound, etc. can be exemplified. Among them, from the viewpoint of being able to improve the water-resistant adhesion with the inorganic film layer by mixing a silicon-based crosslinking agent, a silicon-based crosslinking agent is particularly preferred. In addition, as a crosslinking agent, an oxazoline compound, a carbodiimide compound, an epoxy compound, etc. can also be used in combination.
[0109] As the silicon-based crosslinking agent, from the viewpoint of crosslinking of inorganic and organic substances, a silane coupling agent is preferred. As the silane coupling agent, hydrolyzable alkoxysilane compounds can be cited, for example, halogen-containing alkoxysilanes (chloro C2-4 alkyl tri C1-4 alkoxysilanes such as 2-chloroethyltrimethoxysilane, 2-chloroethyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, etc.), alkoxysilanes having epoxy groups [2-glycidyloxyethyltrimethoxysilane, 2-glycidyloxyethyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, etc.] Glycidyloxy C2-4 alkyl tri C1-4 alkoxysilane, 3-glycidyloxypropyl methyl dimethoxysilane, 3-glycidyloxypropyl methyl diethoxysilane, glycidyloxy di C2-4 alkyl di C1-4 alkoxysilane, 2-(3,4-epoxycyclohexyl) ethyl trimethoxysilane, 2-(3,4-epoxycyclohexyl) ethyl triethoxysilane, 3-(3,4-epoxycyclohexyl) propyl trimethoxysilane, (epoxycycloalkyl) C2-4 alkyl tri C1-4 alkoxysilane, alkoxysilane having an amino group, etc. [2-aminoethyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and other amino C2-4 alkyltriC1-4 alkoxysilanes, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane and other aminodiC2-4 alkyldiC1-4 alkoxysilanes, 2-[N-(2-aminoethyl)amino]ethyltrimethoxysilane, 3-[N-(2-aminoethyl)amino]propyltrimethoxysilane, 3-[N-(2-aminoethyl)amino]propyltriethoxysilane and the like] (2-amino C2-4 alkyl)amino C2-4 alkyltri C1-4 alkoxysilane, 3-[N-(2-aminoethyl)amino]propylmethyldimethoxysilane, 3-[N-(2-aminoethyl)amino]propylmethyldiethoxysilane, (amino C2-4 alkyl)aminodi C2-4 alkyldi C1-4 alkoxysilane, etc.], alkoxysilane having a mercapto group (mercapto C2-4 alkyltri C1-4 alkoxysilane such as 2-mercaptoethyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane;
[0063] The invention also includes mercaptodi C2-4 alkyldi C1-4 alkoxysilanes such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropylmethyldiethoxysilane, etc.), alkoxysilanes having a vinyl group (vinyltrimethoxysilane, vinyltriethoxysilane and other vinyltriC1-4 alkoxysilanes, etc.), alkoxysilanes having an ethylenically unsaturated bond group [2-(meth)acryloxyethyltrimethoxysilane, 2-(meth)acryloxyethyltriethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane and other (meth)acryloxyC2-4 alkyltriC1-4 alkoxysilanes, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane and other (meth)acryloxydi C2-4 alkyldi C1-4 alkoxysilanes, etc.] These silane coupling agents can be used alone or in combination of two or more. Among these silane coupling agents, silane coupling agents having amino groups are preferred. ;
[0110] The silicon-based crosslinking agent is preferably added to the covering layer in an amount of 0.05 to 4.00 mass %, more preferably 0.10 to 3.50 mass %, and further preferably 0.15 to 3.00 mass %. By adding the silicon-based crosslinking agent, the film is cured, the cohesion is improved, and the film is excellent in water-resistant adhesion, and the effect of preventing the exposure of oligomers can also be expected. If the added amount exceeds 3.00 mass %, the film is cured, the cohesion is improved, but a part of the unreacted part is also generated, and the adhesion between the layers may be reduced. On the other hand, if the added amount is less than 0.05 mass %, it is possible that sufficient cohesion cannot be obtained.
[0111] The polyester resin used in the anchor coating (C) of the present invention is manufactured by polycondensation of a polycarboxylic acid component and a polyol component. As for the molecular weight of the polyester resin, there is no particular restriction as long as it can give the film toughness, coating adaptability, and solvent solubility sufficient as a coating material, and the number average molecular weight is 1000 to 50000, and more preferably 1500 to 30000. There is no particular restriction on the functional group at the end of the polyester, and it can be an alcohol end, a carboxylic acid end, or both. However, when an isocyanate curing agent is used in combination, a polyester polyol with an alcohol end as the main body must be used.
[0112] The Tg of the polyester resin used in the anchor coating (C) of the present invention is preferably above 10°C. This is because if the temperature is lower than this, the resin becomes sticky after the coating operation, and adhesion is likely to occur, and the winding operation after coating becomes difficult. This is because if the Tg is below 10°C, even if an anti-adhesion material is added, it is difficult to deal with anti-adhesion under conditions of high pressure near the winding core. The more preferred temperature of Tg is above 15°C, and more preferably above 20°C.
[0113] The polyester resin used in the anchor coating (C) of the present invention is used by condensing a polycarboxylic acid component and a polyol component. The polycarboxylic acid component of the polyester resin used in the present invention is characterized in that it contains at least one of ortho-oriented aromatic dicarboxylic acids or their anhydrides. By setting it to ortho-orientation, the solubility in the solvent is improved, and the substrate can be evenly coated. The deviation of the barrier properties of the uniformly coated film becomes smaller, which helps to suppress oligomerization whitening. In addition, by setting it to ortho-orientation, it becomes a film with excellent flexibility and the interfacial adhesion is improved, so that the damage to the substrate caused by wet heat treatment can be reduced and oligomers can be suppressed.
[0114] As aromatic polycarboxylic acids or their anhydrides substituted with carboxylic acids at the ortho position, phthalic acid or its anhydride, 2,3-naphthalene dicarboxylic acid or its anhydride, 1,2-naphthalene dicarboxylic acid or its anhydride, anthraquinone-2,3-dicarboxylic acid or its anhydride, and 2,3-anthracene dicarboxylic acid or its anhydride can be listed. These compounds can have a substituent on any carbon atom of the aromatic ring. As the substituent, chloro, bromo, methyl, ethyl, isopropyl, hydroxyl, methoxy, ethoxy, phenoxy, methylthio, phenylthio, cyano, nitro, amino, phthalimide, carboxyl, carbamoyl, N-ethylcarbamoyl, phenyl or naphthyl can be listed. In addition, if it is a polyester polyol with a content of 70 to 100 mol% relative to 100 mol% of the total components of these polycarboxylic acids, the barrier property is improved. The effect is high, and the solvent solubility required as a coating material is excellent, so it is particularly preferred.
[0115] In the present invention, other polycarboxylic acid components may be copolymerized within the scope of not impairing the effects of the invention. Specifically, as aliphatic polycarboxylic acids, succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, etc. may be used alone or in the form of a mixture of two or more thereof; as polycarboxylic acids containing unsaturated bonds, maleic anhydride, maleic acid, fumaric acid, etc. may be used alone or in the form of a mixture of two or more thereof; as alicyclic polycarboxylic acids, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, etc. may be used alone or in the form of a mixture of two or more thereof; as aromatic polycarboxylic acids, Polybasic acids such as terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalene dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, diphenyl carboxylic acid and its anhydride, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid and anhydride or ester-forming derivatives of these dicarboxylic acids, p-hydroxybenzoic acid, 4-(2-hydroxyethoxy)benzoic acid and ester-forming derivatives of these dihydroxycarboxylic acids are used alone or in a mixture of two or more thereof. Among them, succinic acid, 1,3-cyclopentane dicarboxylic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, and diphenyl carboxylic acid are preferred from the viewpoint of organic solvent solubility and gas barrier properties.
[0116] The polyol component of the polyester used in the anchor coating (C) of the present invention is not particularly limited as long as a polyester showing gas barrier filling performance can be synthesized, and preferably contains at least one polyol component selected from the group consisting of ethylene glycol, propylene glycol, butanediol, neopentyl glycol, cyclohexanedimethanol and 1,3-bishydroxyethylbenzene. Among them, it is estimated that the smaller the number of carbon atoms between oxygen atoms, the less the molecular chain becomes too soft and the less oxygen permeates, so it is most preferred to use ethylene glycol as the main component.
[0117] In the present invention, the polyol component is preferably used. In addition, other polyol components may be copolymerized within the range that does not impair the effect of the present invention. Specifically, as diols, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methyl pentanediol, dimethyl butanediol, butyl ethyl propanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol can be listed, and as trivalent or higher alcohols, glycerol, trimethylolpropane, trimethylolethane, tris(2-hydroxyethyl)isocyanurate, 1,2,4-butanetriol, pentaerythritol, dipentaerythritol, etc. can be listed. In particular, among the trivalent alcohols, polyesters using glycerol and tris(2-hydroxyethyl)isocyanurate in combination are particularly preferably used because they are derived from a branched structure and have a moderately high crosslinking density, so they have good organic solvent solubility and excellent barrier function.
[0118] As the catalyst used in the reaction to obtain the polyester of the present invention, tin catalysts such as monobutyl tin oxide and dibutyl tin oxide, titanium catalysts such as tetraisopropyl titanate and tetrabutyl titanate, zirconium oxide catalysts such as tetrabutyl zirconate and the like, and acid catalysts such as the like can be cited. It is preferred to use the above-mentioned titanium catalysts such as tetraisopropyl titanate and tetrabutyl titanate, which have high activity in ester reaction, in combination with the above-mentioned zirconium oxide catalyst. The amount of the catalyst is used in an amount of 1 to 1000 ppm relative to the total mass of the reaction raw materials used, and more preferably 10 to 100 ppm. If it is less than 1 ppm, it is difficult to obtain the effect as a catalyst, and if it exceeds 1000 ppm, when an isocyanate curing agent is used, it sometimes occurs that the urethane reaction is hindered.
[0119] In the present invention, when a polyester resin is used as the main agent of the coating agent constituting the anchor coating (C), it is particularly preferred to use an isocyanate curing agent as a curing agent to prepare a polyurethane resin. In this case, the coating becomes a cross-linked system, so it has the advantages of improved heat resistance, wear resistance, and rigidity. Therefore, it is also easy to use for boiling and retorting packaging. On the other hand, there is also the problem that the liquid cannot be recycled after mixing the curing agent, and a curing (ripening) process must be performed after coating. As an advantage, the following aspects can be exemplified: as a simple outer coating varnish, for example, there is no need to worry about the thickening of the coating liquid, the management of the coating manufacturing is easy, the coating liquid can be diluted and recycled, and on this basis, a curing process (so-called aging process) is not required. At this time, the end of the polyester used can be used without any problem, whether it is a polyol, a polycarboxylic acid, or a mixture of the two. On the other hand, since the resin of the coating is a straight chain, sometimes the heat resistance and abrasion resistance are insufficient, and sometimes it is difficult to use for boiling and retorting packaging.
[0120] When a curing agent is used in the coating, since the film is coated, it is preferably an isocyanate curing system from the viewpoint of the heat resistance of the film, and the resin component of the coating material needs to be a polyester polyol. On the other hand, when an epoxy compound is used as a curing agent, it needs to be a polyester polycarboxylic acid. In these cases, the coating becomes a cross-linking system, so it has the advantages of heat resistance, wear resistance, and improved rigidity. Therefore, it is also easy to be used for boiling and steaming packaging. On the other hand, there is also a problem that the liquid cannot be recycled after mixing the curing agent, and a curing (aging) process must be performed after coating.
[0121] The polyisocyanate compound used in the present invention reacts at least partially to form a carbamate structure when the polyester has a hydroxyl group, thereby becoming highly polarized as a resin component, causing polymer chains to condense, thereby further strengthening the gas barrier function. In addition, when the resin of the coating material is a straight-chain resin, heat resistance and wear resistance can be imparted by cross-linking with a polyisocyanate of more than 3 valence. The polyisocyanate compound used in the present invention may be any of a diisocyanate, a polyisocyanate of more than 3 valence, a low molecular weight compound, and a polymer compound, but from the viewpoint of improving the gas barrier function, it is preferred that a portion of the skeleton contains an aromatic ring or an aliphatic ring. For example, examples of isocyanates having an aromatic ring include toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, and naphthalene diisocyanate. Examples of isocyanates having an aliphatic ring include hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, isophorone diisocyanate, and norbornane diisocyanate, or trimers of these isocyanate compounds, and terminal isocyanate group-containing compounds obtained by reacting excess amounts of these isocyanate compounds with low molecular weight active hydrogen compounds such as ethylene glycol, propylene glycol, trimethylolpropane, glycerin, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, and triethanolamine, or high molecular weight active hydrogen compounds such as various polyester polyols, polyether polyols, and polyamides.
[0122] The method for forming the anchor coating (C) is not particularly limited, and a conventionally known method such as a coating method can be used. Suitable methods in the coating method include an offline coating method and an online coating method. For example, in the case of an online coating method performed in the process of manufacturing a substrate film layer, the drying and heat treatment conditions during coating also depend on the coating thickness and the conditions of the device. It is preferred that the coating is immediately fed into a stretching process in a right angle direction and dried in a preheating area or a stretching area of the stretching process. In such a case, it is generally preferred to set the temperature to about 50 to 250°C.
[0123] The coating method of the resin composition for anchor coating (C) is not particularly limited as long as it is a method of coating on the film surface to form a layer. For example, a common coating method such as gravure coating, reverse roll coating, wire bar coating, die coating, etc. can be used.
[0124] When forming the anchor coating (C), it is preferred to heat and dry after applying the anchor coating resin composition. The drying temperature at this time is preferably 100-145°C, more preferably 110-140°C, and further preferably 110-130°C. If the drying temperature is lower than 100°C, the anchor coating may be insufficiently dried. On the other hand, if the drying temperature exceeds 145°C, the film may be overheated, the film may become brittle, or shrink and the processability may deteriorate. In particular, if the solvent is first volatilized at a relatively low temperature of 80°C to 110°C immediately after coating, and then dried at above 120°C, a uniform film can be obtained, which is particularly preferred. In addition, in addition to drying, applying additional heat treatment in a low temperature range as much as possible is also more effective in forming the anchor coating.
[0125] [Protective layer on inorganic thin film]
[0126] In the present invention, a protective layer may be provided on the inorganic thin film layer as a gas barrier layer. By providing a protective layer, processing such as printing can be directly performed on the barrier layer side. However, in the present invention, it is necessary to pay attention to the load on the environment such as the increase in cost due to the increase in the number of steps due to the provision of a protective layer, environmental pollution caused by the use of solvents, and difficulty in recycling due to the film thickness, and design.
[0127] In the present invention, the amount of the protective layer applied is preferably set to 0.10 to 0.40 (g / m 2 ). As a result, the protective layer can be uniformly controlled during coating, resulting in a film with less uneven coating and fewer defects. In addition, the cohesive force of the protective layer (D) itself is improved, and the adhesion between the inorganic thin film layer and the protective layer is also strengthened. The adhesion amount of the protective layer is preferably 0.13 (g / m 2 ) or more, more preferably 0.16 (g / m 2 ) or more, more preferably 0.19 (g / m 2 ) or more, preferably 0.37 (g / m 2 ) or less, more preferably 0.34 (g / m 2 ) or less, more preferably 0.31 (g / m 2 If the adhesion amount of the protective layer (D) exceeds 0.40 (g / m 2 ), the cohesive force inside the protective layer becomes insufficient, and the uniformity of the protective layer is also reduced, so that unevenness or defects may occur in the coating appearance, or the gas barrier property and adhesion cannot be fully exhibited. On the other hand, if the film thickness of the protective layer is less than 0.10 (g / m 2 ), sufficient gas barrier properties and interlayer adhesion may not be obtained.
[0128] As the resin composition used for the protective layer formed on the surface of the inorganic thin film layer of the present invention, resins such as polyvinyl alcohol, urethane, polyester, acrylic, titanium, isocyanate, imine, and polybutadiene can be used, and curing agents such as epoxy, isocyanate, melamine, and silanol can also be added.
[0129] The coating method of the protective layer resin composition is not particularly limited as long as it is a method of coating the film surface to form a layer. For example, a common coating method such as gravure coating, reverse roll coating, wire bar coating, die coating, etc. can be used.
[0130] When forming a protective layer, it is preferred to heat and dry after applying the resin composition for the protective layer. The drying temperature at this time is preferably 100-160°C, more preferably 110-150°C, and further preferably 120-140°C. If the drying temperature is lower than 100°C, the protective layer is insufficiently dried, or the film formation of the protective layer is not carried out, the cohesion and water-resistant adhesion are reduced, and the barrier properties and hand-tear properties may be reduced. On the other hand, if the drying temperature exceeds 160°C, it is possible that excessive heat is applied to the film, the film becomes brittle, the puncture strength is reduced, or the processability is deteriorated due to shrinkage. The protective film is first volatilized at a relatively low temperature of 90°C to 110°C immediately after coating, and then dried at above 130°C, so that a uniform and transparent film can be obtained, so it is particularly preferred. In addition, unlike drying, applying additional heat treatment in a low temperature region as much as possible is also more effective in film formation of the protective layer.
[0131] [Other films]
[0132] In the present invention, within the range of satisfying the single material ratio described later relative to the packaging material, other films other than the base film with polyolefin resin as the main component may be present. Other films used in the present invention are, for example, films obtained by melt-extruding plastics and stretching, cooling, and heat-setting in the length direction and / or width direction as required. As plastics, in addition to polyamides represented by nylon 4.6, nylon 6, nylon 6.6, nylon 12, etc., and polyesters represented by polyethylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalate, etc., polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene vinyl alcohol, wholly aromatic polyamides, polyamide-imides, polyimides, polyetherimides, polysulfones, polystyrene, polylactic acid, etc. may also be cited.
[0133] The other films in the present invention can be used in any thickness according to the desired purpose such as mechanical strength and transparency. Although not particularly limited, 5 to 250 μm is generally recommended, and 10 to 60 μm is ideal when used as packaging materials. However, the ratio of a single material in the packaging material described later needs to be considered.
[0134] In addition, the other films in the present invention can be laminated films of one or more plastic films. The type, number of layers, lamination method, etc. of the laminated body when making the laminated film are not particularly limited and can be arbitrarily selected from known methods according to the purpose.
[0135] [Heat seal resin layer]
[0136] In the packaging material of the present invention, it is necessary to make a laminated body with a heat-sealable resin layer. In the formation of the heat-sealable resin layer, the thermoplastic polymer forming the heat-sealable resin layer is usually laminated by extrusion lamination or dry lamination, but the heat-sealable resin layer can also be coextruded or prepared by coating. As a thermoplastic polymer forming the heat-sealable resin layer, as long as it can fully show adhesion, polyethylene resins such as HDPE, LDPE, LLDPE of the polyolefin system, polypropylene resin, ethylene-vinyl acetate copolymer, ethylene-α-olefin random copolymer, ionomer resin, etc. can be used. Among them, from the viewpoint of durability, sealing strength, price, and single material, LLDPE or polypropylene resin with high versatility is particularly preferred. The thickness of the heat-sealable resin layer is preferably 5 to 100 μm, more preferably 10 to 95 μm, and more preferably 15 to 90 μm. If the thickness is thinner than 5 μm, it may not be possible to obtain sufficient sealing strength, there is no stiffness and it is difficult to handle. On the other hand, when the thickness exceeds 100 μm, the stiffness is strong, the handling property as a bag is reduced, and sealing at a higher temperature is required, which may cause heat wrinkles in the outer base film. In addition, the price may also increase.
[0137] [Adhesive layer]
[0138] The adhesive layer used in the present invention can use a general laminating adhesive. For example, a (non-)solvent type, water-based type, or hot-melt type adhesive with poly (ester) carbamate, polyester, polyamide, polyamine, epoxy, poly (meth) acrylic acid, polyethylene imine, ethylene-(meth) acrylic acid, polyvinyl acetate, (modified) polyolefin, polybutadiene, wax, or casein as the main component can be used. Among them, from the viewpoint of improving heat resistance, flexibility that can follow the dimensional changes of each substrate, and the gas barrier properties of the adhesive itself, it is preferred to make an adhesive formed by cross-linking reaction of polyurethane, polyester, or polyamine resins. However, if the film becomes too hard due to cross-linking, it is worried that the barrier properties after bending will be reduced, so it is necessary to pay attention. In addition, it is also effective to add inorganic substances such as particles to improve barrier properties. As the lamination method of the above-mentioned adhesive layer, for example, direct gravure coating, reverse gravure coating, kiss coating, die coating, roll coating, dip coating, knife coating, spray coating, spinneret coating, other methods can be used for coating, in order to show sufficient adhesion, the thickness after drying is preferably 1 to 8 μm. More preferably 2 to 7 μm, further preferably 3 to 6 μm. If the coating amount is less than 1 μm, it is difficult to fit on the entire surface, and the bonding force is reduced. In addition, if it exceeds 8 μm, the complete curing of the film takes time, unreacted products are easily left, and the bonding force is reduced.
[0139] [Printing layer]
[0140] Furthermore, in the packaging material of the present invention, at least one printed layer may be laminated between the substrate film layer and the heat-sealable resin layer or on the outside thereof. However, in the case of direct printing on the inorganic film layer, the inorganic film layer is scraped off by the pigment in the ink, and the barrier may be deteriorated, so it is preferred to provide a protective layer. In the case of providing a printed layer on the barrier layer, the penetration effect of the adhesive layer described later on the barrier layer may be reduced, so in the case of attaching importance to the barrier performance, the printed layer is preferably provided on another surface in a manner that does not directly contact the barrier layer.
[0141] As the printing ink for forming the printing layer, water-based and solvent-based resin-containing printing inks can be preferably used. Here, as the resin used in the printing ink, acrylic resins, urethane resins, polyester resins, vinyl chloride resins, vinyl acetate copolymer resins and mixtures thereof can be exemplified. The printing ink may contain known additives such as antistatic agents, light shielding agents, ultraviolet absorbers, plasticizers, lubricants, fillers, colorants, stabilizers, lubricants, defoamers, crosslinking agents, anti-blocking agents, antioxidants, etc. As the printing method for setting the printing layer, it is not particularly limited, and known printing methods such as offset printing, gravure printing, and screen printing can be used. The drying of the solvent after printing can use known drying methods such as hot air drying, hot roller drying, and infrared drying.
[0142] [Characteristics of packaging materials]
[0143] As the packaging material of the present invention, any conceivable laminated structure can be used. As described above, from the viewpoint of improving toughness and gas barrier performance, for example, as one of the preferred structures, a laminated body in which a film laminated with a gas barrier layer is sandwiched between a base film without a gas barrier layer and a thermoplastic copolymer with a heat-sealing resin layer can be cited. At this time, by laminating the printed layer on the base film on the outside, the advantage of not having to print on a film with a gas barrier layer can also be improved. In addition, laminating with a white base film, a heat-sealing resin layer to improve concealment, or laminating with an ultraviolet cut-off film for light-shielding properties is also one of the suitable structures.
[0144] The packaging material of the present invention is a laminated packaging material having an adhesive layer, a heat-sealable resin layer and at least one substrate film, wherein the substrate film has a resin layer having a polyolefin resin as a main component. Furthermore, at least one of the substrate films is a laminated gas barrier film having a gas barrier layer. It is characterized in that the oxygen permeability value (A) measured under 23°C × 65%RH for the substrate film (a) having the lowest oxygen permeability among the substrate films alone needs to be 30 to 1500 ml / m 2 ·d·MPa, when the value of oxygen permeability measured under the same conditions for a laminated packaging material (p) in which a base film and a heat-sealable resin are laminated via an adhesive layer is defined as (P), the barrier value improvement rate before and after lamination represented by the following formula (1) is 10 or more.
[0145] Barrier value improvement rate before and after film lamination = (A / P) ... Formula (1)
[0146] In the present invention, it is found that the oxygen barrier performance of the film used is set within the above range, and the barrier performance is greatly improved when it is laminated with other films by means of an adhesive. The oxygen barrier property of the polypropylene film itself is very poor, so even if there are small defects in the barrier layer, the oxygen permeability is worse than that of the polyester film used as the substrate. By filling the defect with an adhesive, the barrier performance can be filled, but it is found that the barrier repair effect is highest in the area where there are defects to a certain extent in the barrier layer (that is, the oxygen permeability (A) of the substrate film (a) is in the above range). The reason is still uncertain, but it is believed that by the presence of a certain degree of defects, the adhesive is uniformly infiltrated into the substrate interface (the area where the barrier film is sparse) through the barrier layer, which has the effect of improving the barrier performance of the entire film. Therefore, it is believed that the barrier performance of the same level as the barrier performance exhibited by stacking multiple barrier layers in the form of a film monomer can be achieved with a small barrier layer.
[0147] The barrier film has a certain degree of defects in the barrier layer, and has the advantages that the film has low density, so it has flexibility and improves resistance to stress loads such as bending. The present invention is characterized in that the oxygen permeability value (G) of the laminated packaging material after 50 twist bending tests at a temperature of 23°C using a rubbing tester is 70 ml / m 2 ·d·MPa or less. By setting the oxygen permeability G within the above range, a packaging material having excellent bending resistance can be obtained.
[0148] Furthermore, by making the oxygen permeability (A) of the substrate film (a) within the above range, the residual solvent and reaction gas generated by the adhesive can be rapidly diffused (escape from the film). Thus, the curing reaction of the adhesive is promoted, and the effect of shortening the aging during lamination can be expected. In addition, a packaging material with excellent appearance and no bubbles in the laminate can be made. In particular, when an adhesive with a large barrier improvement effect is used, the volatile components have more time to diffuse, so the effect of the present invention becomes greater. The time required for the volatile components to completely evaporate can be measured by tracking the volatilization amount of the volatile components by weight change immediately after the laminated packaging material (p) formed by bonding the substrate film and the heat-sealing resin with the aid of an adhesive is made. In the present invention, the time required for the volatile components to disappear is preferably within 30 hours. More preferably, it is within 25 hours, and further preferably within 20 hours.
[0149] The oxygen permeability (A) of the substrate film (a) is preferably 33 to 1350 ml / m 2 ·d·MPa, more preferably 36 to 1200 ml / m 2 ·d·MPa, more preferably 39 to 1050 ml / m 2 ·d·MPa. Oxygen permeability (A) less than 30ml / m 2 When the barrier layer has a density of 1500 ml / m2, the barrier performance of the single body is improved due to the decrease in defects of the barrier layer. However, the barrier performance improvement effect when the packaging material is made may be reduced, and the bending resistance barrier may also be deteriorated. Furthermore, it takes a longer time for the volatile components of the adhesive to be released. On the other hand, the oxygen permeability (A) is greater than 1500 ml / m2. 2 When the thickness is 2.5 d·MPa, there are too many defects and the film may not function as a barrier film after being laminated to form a packaging material.
[0150] The barrier value improvement ratio (A / P) before and after film lamination is preferably 25 or more, more preferably 50 or more, and further preferably 75 or more. When (A / P) is less than 10, the barrier performance improvement effect when used as a packaging material becomes small, and there is a possibility that the bending resistance barrier property deteriorates and the amount of residual volatile components increases.
[0151] The oxygen permeability of the packaging material of the present invention under the conditions of 23°C×65%RH is 60ml / m 2 ·d·MPa or less, which is necessary to show good gas barrier properties. More preferably, it is 50ml / m 2 ·d·MPa or less, more preferably 40ml / m 2 ·d·MPa or less. If the oxygen permeability exceeds 60ml / m 2 On the other hand, if the oxygen permeability is less than 0.5 ml / m 2 ·d·MPa, although the barrier performance is excellent, it is difficult for the residual solvent to penetrate to the outside of the bag, and the amount of transfer to the contents may increase relatively, which is not preferred. The preferred lower limit of oxygen permeability is 0.5ml / m 2 ·d·MPa or more.
[0152] The water vapor permeability of the packaging material of the present invention at 40°C × 90% RH is 5.0 g / m 2 ·d or less, which is preferred in terms of exhibiting good gas barrier properties. More preferably, it is 4.0 g / m 2 ·d or less, more preferably 3.0 g / m 2 ·d or less. Water vapor transmission rate exceeds 5.0g / m 2 ·d, it is difficult to cope with applications requiring high gas barrier properties. On the other hand, the water vapor transmission rate is less than 0.1 g / m 2 Although the barrier performance is excellent, it is difficult for the residual solvent to penetrate to the outside of the bag, and the amount of transfer to the contents may increase relatively, which is not preferred. The preferred lower limit of water vapor permeability is 0.1 g / m 2 d or above.
[0153] As an evaluation criterion for the monomaterialization of the packaging material of the present invention, when the ratio of the thickness of the polyolefin raw material to the total thickness of each film and the adhesive is calculated as the monomaterial ratio, the monomaterial ratio is preferably 70% or more. More preferably, it is 80% or more, and further preferably, it is 90% or more. By setting the monomaterial ratio to this range, a packaging material structure that is easily recycled can be formed. If the monomaterial ratio is less than 70%, it may be difficult to recycle due to foreign matter from different raw materials.
[0154] It should be noted that, as described above, polypropylene resin is preferably used as the polyolefin resin constituting the substrate film, but if the heat sealable resin layer also uses polypropylene resin, it can be made into a structure that is more easily recycled. If all the polyolefin raw materials used are polypropylene resin, it can be made into a structure that is further easily recycled.
[0155] In the packaging material of the present invention, the total thickness of each film and adhesive is preferably 20 to 140 μm. It is more preferably 25 to 135 μm, and further preferably 30 to 130 μm. By making the total thickness of the packaging material within this range, a packaging body that can exhibit necessary physical properties such as toughness and barrier properties can be made. If the total thickness is less than 20 μm, the toughness as a bag is insufficient, and the bag may be broken or have holes. On the other hand, if the total thickness exceeds 140 μm, not only will the stiffness become stronger and difficult to handle, but the cost as a packaging body will increase, which is not economically preferred.
[0156] As described above, the packaging material of the present invention has excellent barrier properties, and also excellent visibility and bending resistance, and can be used as various packaging bodies. Examples of packaging bodies include sterilization by boiling or steaming, frozen food use, vacuum packaging use, microwave heating use, and the like.
[0157] The form of the package using the packaging material of the present invention is not particularly limited, and may be in various forms. Examples of the packaging form include three-sided / four-sided bags, stand-up bags, spout bags, and the like.
[0158] The content filled in the packaging bag using the packaging material of the present invention is not particularly limited, and the content may be liquid, powder, or gel. In addition, it may be food or not.
[0159] Example
[0160] Next, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples. It should be noted that various evaluations were performed by the following measuring methods.
[0161] (1)Thickness of various films
[0162] The measurement was performed using a micrometer in accordance with JIS K7130-1999 A method.
[0163] (2) Composition and thickness of the inorganic thin film layer (B)
[0164] The film thickness composition of the laminated thin films obtained in Examples and Comparative Examples (after film lamination) was measured using an X-ray fluorescence analyzer ("supermini200" manufactured by Rigaku Corporation) according to a pre-made calibration curve. The conditions for exciting the X-ray tube were 50 kV and 4.0 mA.
[0165] (3) Adhesion amount of cover layer (A) and anchor coating (C)
[0166] In each embodiment and comparative example, each laminated film obtained at the stage where a specified covering layer (A) and an anchor coating (C) are laminated on a base film is used as a sample, and a 100 mm × 100 mm test piece is cut out from the sample. The coating is wiped with water, ethanol or acetone, and the adhesion amount is calculated from the change in mass of the film before and after wiping.
[0167] (4) Method for evaluating oxygen permeability (A) of substrate film (a)
[0168] The oxygen permeability of the substrate film (a) having the lowest oxygen permeability among the substrate films used in the examples and comparative examples was measured in accordance with JIS-K7126 B method using an oxygen permeability measuring device ("OX-TRAN (registered trademark) 2 / 22" manufactured by MOCON) in an atmosphere of 23°C and 65%RH. It should be noted that the oxygen permeability was measured in the direction of oxygen permeation from the side where the coating layer was not laminated to the coating layer.
[0169] [Production of packaging materials]
[0170] (5) Preparation of packaging materials for evaluation
[0171] When there is one substrate film, various adhesives are applied to the substrate film described in the embodiments and comparative examples in such a manner that the thickness becomes 3 μm after drying at 80°C, and then an unstretched polypropylene film or a linear low-density polyethylene film described below as a heat-sealable resin is dry-laminated on a metal roller heated to 60°C and aged at 40°C for more than 96 hours to obtain a laminated stack for evaluation.
[0172] On the other hand, when there are two substrate films, various adhesives are applied to the substrate films described in the examples and comparative examples so that the thickness becomes 3 μm after drying at 80°C, and the other substrate film is dry-laminated on a metal roll heated to 60°C to prepare a take-up roll. The same adhesive is applied to the roll so that the thickness becomes 3 μm after drying at 80°C, and then an unstretched polypropylene film (CPP1) or a linear low-density polyethylene film described below as a heat-sealable resin is dry-laminated on a metal roll heated to 60°C, and aged at 40°C for more than 96 hours to obtain a packaging material for evaluation.
[0173] In addition, any of the following three types of adhesives were used. Table 1 shows the blending ratio of each material.
[0174] Adhesive 1: Main agent A: Polyamine / Curing agent A: Epoxy curing adhesive (Mitsubishi Gas Chemical Co., Ltd. C93 / M100)
[0175] Adhesive 2: Main agent B: polyester / Curing agent B: isocyanate curing adhesive (VM001 / VM108CP manufactured by DIC Corporation)
[0176] Adhesive 3: Main agent C: polyester / Curing agent C: isocyanate curing adhesive (TM569 / cat10L manufactured by Toyo-Morton Co., Ltd.)
[0177] (6) Evaluation method of oxygen permeability of packaging materials
[0178] The packaging material prepared in (5) above was measured for oxygen permeability in an atmosphere of 23° C. and 65% RH using an oxygen permeability measuring apparatus (“OX-TRAN (registered trademark) 2 / 22” manufactured by MOCON) according to JIS-K7126 B method. It should be noted that the measurement of oxygen permeability was conducted in the direction of oxygen permeation from the base film side of the packaging material to the heat-sealable resin layer side.
[0179] (7) Method for evaluating oxygen permeability of packaging materials after bending test
[0180] The packaging material prepared in the above (5) was made into a sample piece of 112 inches × 8 inches, formed into a cylindrical shape with a diameter of 3 (1 / 2) inches and mounted on a rubbing tester (MIL-B131H manufactured by Rigaku Kogyo Co., Ltd.), held at both ends, with the initial gripping interval set to 7 inches, and a 400 degree twist was applied at 3 (1 / 2) inches of the stroke, and this action was repeated 25 times at a speed of 50 times / minute under the conditions of 23°C and a relative humidity of 65%. The oxygen permeability (after bending treatment) of the packaging material obtained after the bending test was measured in the same manner as above.
[0181] (8) Evaluation method of water vapor permeability of packaging materials
[0182] The packaging material prepared in (5) above was measured for water vapor permeability in an atmosphere of 40°C and 90%RH using a water vapor permeability measuring apparatus ("PERMATRAN-W 3 / 33MG" manufactured by MOCON) according to JIS-K7129 B method. It should be noted that the water vapor permeability was measured in the direction of water vapor permeation from the base film side of the packaging material to the heat sealable resin side.
[0183] (9) Method for evaluating the time required for the volatile components of packaging materials to disappear
[0184] The packaging material prepared in (5) above was prepared into a 10 cm square sample, and the weight of the sample was measured immediately after dry lamination. The sample was stored in an environment of 40°C, and the weight was measured every 5 hours to confirm the change. The time from immediately after dry lamination until the weight stopped changing was taken as the time required for the volatile components to disappear.
[0185] (10) Evaluation criteria for single material: Single material ratio
[0186] For the packaging material produced in the above (5), as a standard for evaluating the monomaterialization, the ratio of the thickness of the olefin-based raw material to the total thickness of each film and the adhesive was calculated as a monomaterial ratio.
[0187] (11) Evaluation criteria for visual recognition and range adaptability
[0188] For the packaging materials produced in the above (5), as the evaluation criteria for visual recognition and range adaptability, those whose packaging bodies were transparent and whose barrier layers did not use aluminum foil or aluminum vapor deposition were scored as 0.
[0189] The base film used in the present example and the comparative example is described below. It should be noted that the base film used in Examples 1 to 12 and Comparative Examples 1 to 4 is shown in Table 6.
[0190] [Production of substrate film]
[0191] Tables 1 to 4 show the details of the polypropylene resin raw materials used in the production of the polyolefin substrate films OPP-1 to 4, the film forming conditions, and the raw material blending ratios.
[0192] [Table 1]
[0193]
[0194] [Table 2]
[0195]
[0196] [Table 3]
[0197] Film Forming Conditions <![CDATA[ a ]]> b Molten resin temperature (℃) 250 250 Cooling roller temperature (℃) 40 30 Longitudinal stretching ratio (times) 4.5 4.5 Longitudinal stretching temperature (℃) 125 125 Stretching ratio in width direction (times) 8.2 8.2 Width direction stretching preheating temperature (℃) 167 168 Stretching temperature in width direction (℃) 163 155 Heat setting temperature(℃) 169 165 Relaxation rate in width direction (%) 6.7 6.7
[0198] [Table 4]
[0199]
[0200] (OPP-1)
[0201] In the substrate layer (A), 30 wt% of a propylene homopolymer (PP "FS2012" manufactured by Sumitomo Chemical Co., Ltd.: comonomer content: 0 mol%; hereinafter referred to as "PP-2") having Mn = 81,000, Mw = 320,000, MFR = 2.2 g / 10 min, and meso pentad content [mmmm] = 99.2% as shown in Table 1, and 70 wt% of a propylene homopolymer (PP "FLX80E4" manufactured by Sumitomo Chemical Co., Ltd.: comonomer content: 0 mol%; hereinafter referred to as "PP-3") having Mn = 65,000, Mw = 240,000, MFR = 7.5 g / 10 min, and meso pentad content [mmmm] = 98.9% were used.
[0202] In addition, the surface layer (B) used a material in which a propylene polymer having Mn=55,000, Mw=300,000, and MFR=5.6 g / 10 min (NOVATEC (registered trademark) PP "FL4" manufactured by Japan Polypropylene Co., Ltd.: abbreviated as "PP-5") was mixed with 24.8 wt% of a propylene polymer having Mn=59,000, Mw=310,000, and MFR=5.3 g / 10 min (Prime Polypro "F-300SP" manufactured by Prime Polymer Co., Ltd.: abbreviated as "PP-6") and 3.0 wt% of the masterbatch A shown in Table 2 was mixed.
[0203] The base layer (A) was extruded by a 45 mm extruder, the surface layer (B) was extruded by a 25 mm extruder, and the second surface layer (B) was extruded by a 20 mm extruder. The raw resins were melted at 250°C, co-extruded into sheets through a T die, and the surface layer (B) was cooled and solidified in such a way that it was in contact with a cooling roll at 40°C, and then stretched to 4.5 times in the longitudinal direction (MD) at 125°C. Then, in a tenter, the film was clamped at both ends in the width direction (TD) with a clamp, preheated at 174°C, stretched to 8.2 times in the width direction (TD) at 158°C, relaxed by 6.7% in the width direction (TD), and heat-set at 175°C. The film-forming conditions at this time are recorded as film-forming conditions a.
[0204] In this way, a biaxially oriented polypropylene film having a structure of surface layer (B) / base layer (A) / second surface layer (B) was obtained.
[0205] The surface of the surface layer (B) of the biaxially oriented polypropylene film was subjected to corona treatment using a corona treatment machine manufactured by SOFTAL Corona & Plasma GmbH under the condition of applying a current value of 0.75 A, and then wound up with a reel. The thickness of the obtained film was 20 μm (the thickness of the surface layer (B) / substrate layer (A) / second surface layer (B) was 1.0 μm / 18.0 μm / 1.0 μm). The details of this structure are shown in Table 4.
[0206] (OPP-2)
[0207] In the substrate layer (A), 100 wt% of a propylene homopolymer (PP "FL203D" manufactured by Japan Polypropylene Co., Ltd.: comonomer content 0 mol%; hereinafter referred to as "PP-1") having Mn = 56,000, Mw = 310,000, MFR = 2.5 g / 10 min, and meso pentad fraction [mmmm] = 94.8% as shown in Table 1 was used, and in the surface layer B, 95.2 wt% of PP-1 and 4.8 wt% of master batch B were blended, and a film was formed under the conditions of b in Table 3. Except for this, the same conditions as OPP1 were used to obtain a 20 μm biaxially oriented polypropylene film. The details of this structure are shown in Table 4.
[0208] (OPP-3)
[0209] In the substrate layer (A), 27.0 wt% of the polypropylene homopolymer PP-2 shown in Table 1, 70.0 wt% of the polypropylene homopolymer PP-3 shown in Table 1, and 3 wt% of [PE-1: ethylene homopolymer "SLH218" manufactured by Braskem, MFR: 2.3 g / 10 min, melting point: 126°C, bio-based content: 84%, density: 0.916 g / cm3] were mixed, and the same conditions as those of OPP-1 were used to obtain a 20 μm biaxially oriented polypropylene film. The details of this structure are shown in Table 4.
[0210] (OPP-4)
[0211] The surface layer (C) was prepared by mixing 52.0 wt% of a propylene-ethylene copolymer (WINTEC (registered trademark) PP "WFX4M" manufactured by Japan Polypropylene Co., Ltd.: abbreviated as "PP-4") having Mn = 80,000, Mw = 220,000, and MFR = 7.0 g / 10 minutes as shown in Table 1, 45.0 wt% of PP-1, and 3.0 wt% of a master batch A as shown in Table 2. The same conditions as those of OPP1 were used to obtain a 20 μm biaxially oriented polypropylene film. The details of this structure are shown in Table 4.
[0212] (OPP-5)
[0213] The substrate layer (A) was prepared under the same conditions as OPP-2 except that 99.0 wt% of PP-1 and 1.0 wt% of stearyl diethanolamine stearate (KYM-4K manufactured by Matsumoto Oil & Fats Co., Ltd.) as an antistatic agent were blended. A 20 μm biaxially oriented polypropylene film was obtained. The details of this structure are shown in Table 4.
[0214] (Other substrate films)
[0215] (Vapor-deposited PET) Transparent vapor-deposited polyester film with a thickness of 12 μm ("VE100-12 μm" manufactured by Toyobo)
[0216] (Cover layer (A))
[0217] The coating liquid for forming the covering layer (A) used in the present example and the comparative example is described below in detail.
[0218] [Polyvinyl alcohol resin (a)]
[0219] 10 parts by mass of a completely saponified polyvinyl alcohol resin (manufactured by Nippon Synthetic Chemical Co., Ltd., trade name: G-POLYMER OKS8049Q, (saponification degree 99.0% or more, average degree of polymerization 450) was added to 90 parts by mass of purified water, heated to 80°C while stirring, and then stirred for about 1 hour. Then, the mixture was cooled to room temperature, thereby obtaining a substantially transparent polyvinyl alcohol solution (PVA solution) having a solid content of 10%.
[0220] [Inorganic layered compound dispersion (b)]
[0221] 5 parts by mass of collodionite (trade name: KUNIPIAF, manufactured by Kunimine Industries Co., Ltd.) as an inorganic layered compound was added to 95 parts by mass of purified water while stirring, and fully dispersed using a homogenizer at 1500 rpm. The mixture was then kept at 23°C for 1 day to obtain an inorganic layered compound dispersion having a solid content of 5%.
[0222] [Coating liquid 1 for cover layer 1]
[0223] The respective materials were mixed at the following blending ratio to prepare a coating liquid (resin composition for a cover layer).
[0224]
[0225] (Coating of coating liquid on film (lamination of cover layer))
[0226] The coating solution prepared above was applied to the corona treated surface of the substrate film by gravure roll coating, pre-dried at 90°C for 4 seconds, and then dried at 120°C for 4 seconds to obtain a covering layer. The adhesion amount of the covering layer at this time was 0.30 g / m 2 Then, a post-heat treatment was performed at 40° C. for 2 days (48 hours). In the above manner, a laminated film having a cover layer was produced.
[0227] (Inorganic thin film layer (B))
[0228] The following describes the method for producing the inorganic thin film layer (A) used in each example and comparative example. It should be noted that the inorganic thin film layer (A) used in Examples 1 to 12 and Comparative Examples 1 to 7 is shown in Table 5.
[0229] (Formation of Inorganic Thin Film Layer 1)
[0230] As the inorganic thin film layer 1, a composite oxide layer of silicon dioxide and aluminum oxide is formed on the substrate film or the anchor coating by electron beam evaporation. As the evaporation source, granular SiO2 (purity 99.9%) and A12O3 (purity 99.9%) of about 3 mm to 5 mm are used. The film thickness of the inorganic thin film layer (SiO2 / A12O3 composite oxide layer) in the thin film (inorganic thin film layer / thin film containing a covering layer) thus obtained is 13 nm. In addition, the composition of the composite oxide layer is SiO2 / A12O3 (mass ratio) = 70 / 30.
[0231] (Formation of Inorganic Thin Film Layer 2)
[0232] Silicon oxide was deposited on the substrate film or the anchor coat layer as the inorganic thin film layer 2. A small vacuum deposition apparatus (VWR-400 / ERH manufactured by ULVAC KIKO, INC.) was used and the pressure was reduced to 10 -3 After Pa, silicon monoxide was placed on a Nilaco vapor deposition source B-110 from the bottom of the substrate and heated to evaporate, thereby forming a silicon oxide film with a thickness of 30 nm on the thin film.
[0233] (Formation of Inorganic Thin Film Layer 3)
[0234] As the inorganic thin film layer 3, metal aluminum was deposited on the substrate film or the anchor coating layer. A small vacuum deposition device (VWR-400 / ERH manufactured by ULVAC KIKO, INC.) was used and the pressure was reduced to 10 -3 After Pa, an aluminum foil with a purity of 99.9% was placed on a Nilaco vapor deposition source CF-305W from the bottom of the substrate, and the metal aluminum was heated and evaporated to form a metal aluminum film with a thickness of 30 nm on the thin film.
[0235] (Formation of Inorganic Thin Film Layer 4)
[0236] As the inorganic thin film layer 4, aluminum oxide is vapor-deposited on the substrate film or the anchor coating. As a method for vapor-depositing aluminum oxide on the substrate film layer, the film is placed on the unwinding side of a continuous vacuum vapor deposition machine, and the film is moved by means of a cooling metal roller to wind up the film. At this time, the continuous vacuum vapor deposition machine is depressurized to 10 -4 Torr or less, metallic aluminum with a purity of 99.99% is loaded into an alumina crucible from the bottom of the cooling drum, the metallic aluminum is heated and evaporated, and oxygen is supplied to its vapor to cause an oxidation reaction, while it adheres and accumulates on the thin film to form an aluminum oxide film with a thickness of 10nm.
[0237] (Anchor coating (C))
[0238] The following describes the method for producing the anchor coating layer (C) used in each of the Examples and Comparative Examples.
[0239] [Polyester resin (a)]
[0240] As the polyester component, polyester polyol ("DF-COAT GEC-004C" manufactured by DIC Corporation: solid content 30%) was used.
[0241] [Polyisocyanate crosslinking agent (b)]
[0242] As the polyisocyanate component, a trimethylolpropane adduct of meta-xylylene diisocyanate ("TAKENATE D-110N" manufactured by Mitsui Chemicals, Inc.: solid content 75%) was used.
[0243] [Silane coupling agent (c)]
[0244] As a silane coupling agent, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane ("KBM-603" manufactured by Shin-Etsu Chemical Co., Ltd.) was used.
[0245] [Coating liquid 1 for anchor coating layer 1]
[0246] A solution (15% by mass) of a silane coupling agent (c) dissolved in acetone and an isocyanate (b) were mixed at the following ratio and stirred for 10 minutes using a magnetic stirrer. The resulting mixture was diluted with methyl ethyl ketone and 1-methoxy-2-propanol (hereinafter referred to as PGM), and a polyester resin (a) was further added to obtain a target coating solution 1.
[0247] The mixing ratio is shown below.
[0248]
[0249] (Coating of coating liquid to film (lamination of anchor coating layer))
[0250] The coating solution 1 was applied to the corona-treated surface of the substrate film by gravure roll coating, and then pre-dried at 95°C for 4 seconds and then mainly dried at 115°C for 4 seconds to obtain an anchor coating. The adhesion amount of the anchor coating at this time was 0.40 g / m 2 Then, a post-heat treatment was performed at 40° C. for 4 days (96 hours) to obtain the target laminated film.
[0251] As described above, packaging materials were prepared which had a cover layer, an anchor coating layer, an inorganic thin film layer or a protective layer on each film, and further had a heat-sealable resin.
[0252] [Table 5]
[0253]
[0254] In each of the Examples and Comparative Examples, each packaging body was used and bonded by dry lamination using the above-mentioned adhesive to produce a packaging material having a structure described in Table 6. In addition, any of the following was used as the heat-sealable resin layer.
[0255] (Heat seal resin)
[0256] (CPP1) Unstretched polypropylene film with a thickness of 30 μm ("P1128" manufactured by Toyobo Co., Ltd.). The structure of the produced package is shown in Table 6. Various evaluations were performed on the obtained package. The results are shown in Table 6.
[0257] [Table 6A]
[0258]
[0259] [Table 6B]
[0260]
[0261] Industrial Applicability
[0262] According to the present invention, it is found that by making a packaging material obtained by laminating a prescribed barrier layer that meets the required performance on a polyolefin-based substrate film, the gas barrier performance can be greatly improved, and the durability that can withstand the stress load during processing can be ensured. Finally, by laminating a sealant containing an olefin component, it is possible to contribute to the single material while maintaining high sealing. Moreover, the packaging material of the present invention can be made into a packaging body with less volatile components, less food transfer, and less appearance defects. In addition, there are fewer processing steps and it can be easily manufactured, and the volatile components are also quickly separated, so both economy and production stability are excellent, and a gas barrier packaging body with homogeneous characteristics can be provided.
Claims
1. A laminated packaging material, characterized in that: The present invention relates to a laminated packaging material having an adhesive layer, a heat-sealable resin layer and at least one substrate film, wherein the substrate film has a resin layer with a polyolefin resin as a main component, at least one of the substrate films is a laminated gas barrier film having a gas barrier layer, and the oxygen permeability value (A) measured under the conditions of 23°C × 65%RH for the substrate film (a) with the lowest oxygen permeability among the laminated substrate films alone is 30 to 1500 ml / m 2 ·d·MPa, under the same conditions, the oxygen permeability value (P) of the laminated packaging material (p) formed by laminating the base film and the heat-sealing resin via the adhesive layer was 60 ml / m 2 ·d·MPa or less, the barrier value improvement rate before and after lamination represented by the following formula (1) is 10 or more, Barrier value improvement rate before and after film lamination = (A / P) ... formula (1).
2. The laminated packaging material according to claim 1, characterized in that: The oxygen permeability value (G) of the laminated packaging material after 25 times of twist bending test at 23°C using a rubbing tester was 65 ml / m 2 ·d·MPa or less.
3. The laminated packaging material according to claim 1 or 2, characterized in that: The time required from immediately after the production of the laminated packaging material (p) in which the base film and the heat-sealing resin are bonded together via an adhesive until the volatile components cease to volatilize is within 30 hours.
4. The laminated packaging material according to any one of claims 1 to 3, wherein The substrate film comprises the substrate film (a) and another substrate film (b), wherein the substrate film (b) is a laminated barrier film having a resin layer and a gas barrier layer, and the resin layers constituting the substrate film (a) and the substrate film (b) have the same polyolefin resin as the main constituent component.
5. The laminated packaging material according to any one of claims 1 to 4, characterized in that: There are two or less of the substrate films.
6. The laminated packaging material according to any one of claims 1 to 5, wherein The resin layer constituting the base film and the heat-sealable resin layer have the same polyolefin-based resin as a main constituent component.
7. The laminated packaging material according to any one of claims 1 to 6, characterized in that: The adhesive layer is formed of any one of polyurethane-based, polyester-based, or polyamine-based resins.
8. The laminated packaging material according to any one of claims 1 to 7, characterized in that: The gas barrier layer is an inorganic thin film layer formed of any one of aluminum, aluminum oxide, silicon oxide, or a composite oxide of silicon oxide and aluminum oxide.
9. The laminated packaging material according to any one of claims 1 to 8, characterized in that: The gas barrier layer is a covering layer formed of any one of polyvinyl alcohol resin, polyester resin or polyurethane resin.
10. The laminated packaging material according to any one of claims 1 to 9, characterized in that: An anchor coating layer is laminated between the base film and the gas barrier layer.
11. The laminated packaging material according to any one of claims 1 to 10, characterized in that: For boiling or steaming purposes.
12. The packaging material according to any one of claims 1 to 10, characterized in that: For microwave heating purposes. 13 . A packaging bag, comprising the laminated packaging material according to claim 1 . 14 . A packaging body obtained by packaging an object using the laminated packaging material according to claim 1 or the packaging bag according to claim 13 .
Citation Information
Patent Citations
Composite film and production thereof
JP1992359033A
Laminate and its manufacture
JP2000052501A
Body warmer packaging film
JP2003231221A
Polyester film for sealant, laminate and package
JP2017165059A
Laminated polypropylene film
WO2017221781A1